The black tides of heaven eaudiobook - Yang, Neon (Tensorate, 2019)
Mokoya and Akeha, the twin children of the Protector, were sold to the Grand Monastery as infants. While Mokoya developed her strange prophetic gift, Akeha was always the one who could see the strings that moved adults to action. While Mokoya received visions of what would be, Akeha realized what could be. What's more, they saw the sickness at the heart of their mother's Protectorate. A rebellion is growing. The Machinists discover new levers to move the world every day, while the Tensors fight to put them down and preserve the power of the state. Unwilling to continue as a pawn in their mother's twisted schemes, Akeha leaves the Tensorate behind and falls in with the rebels. But every step Akeha takes towards the Machinists is a step away from Mokoya. Can Akeha find peace without shattering the bond they share with their twin?